Alternativas para mitigar el impacto en el uso de glifosato, herbicida altamente tóxico empleado en la agricultura en México - Sánchez-Fabila, Barbara Michelle (2025)
Agriculture is one of the most important activities worlwide, responsible for providing raw materials and food. The demand for food has increased in recent years, and with it the implementation of products that enhance the efficiency of crops. Among the main products used in this industry are pesticides (insecticides, fungicides, and herbicides) and synthetic fertilizers. The use of these compounds has risen alarmingly and sometimes excessively in recent decades, contributing to the development of resistance in harmful species such as bacteria, fungi, and weeds and require higher concentrations or more harmful compounds. Another concern is the collateral exposure that humans have to these compounds, which causes serious health problems. There are multiple reports about the toxic and carcinogenic effects of these compounds, as documented in this paper, particularly about the use of a highly toxic herbicide in Mexico and the world called glyphosate. Finally, alternatives are offered for the elimination of this compound, based on techniques ranging from bioremediation to others using cutting-edge technologies, such as the use of nanomaterial, even for environmental monitoring.